Differences in Health-Related Quality of Life Predictors in People Living With HIV With and Without Diabetes. (25th September 2020) - Zuñiga, Julie Ann; Jang, Dong Eun; Walker, Gregory; Ohueri, Chelsi West; A. García, Alexandra
Abstract: Diabetes is one of the most common comorbid conditions in people living with HIV (PLWH). Diabetes may affect health-related quality of life (HRQoL) for PLWH because they experience more symptoms, are prescribed more medications, and are required to do self-care activities. The purpose of our study was to compare predictors of the HRQoL for PLWH with and without diabetes. The study was a secondary analysis of data from the Center for AIDS Research Network of Integrated Clinical Systems cohort using multiple regression. Significant differences were found between PLWH with and without diabetes. The significant predictors of HRQoL for PLWH-alone were depression, anxiety, medication adherence, physical activity, smoking, and age. For PLWH with diabetes, the only significant predictors of HRQoL were anxiety and depression.